Interactive Solar System Media as Teacher's Aid for Elementary Students - Aniek Suryanti Kusuma; Welda Welda; I Ketut Agus Sanjaya Damu (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
The primary challenge in teaching science on the topic of the solar system at the elementary school level lies in the abstract nature of its concepts, which are difficult to visualize using conventional media. This condition may lead to monotonous learning and student misconceptions. This study aims to develop an interactive multimedia-based teaching medium to address these issues. The research employed the Research and Development (R&D) method utilizing the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), with the implementation focused up to the Development and Formative Evaluation stages. The medium was developed based on a needs analysis conducted at SD Pelangi Jimbaran, resulting in a prototype with a complete structure comprising an opening page, main menu, instructions, video materials, and an evaluation quiz. Validation results from subject matter experts and media experts indicated a very high level of feasibility, with scores of 84% and 86%, respectively. The study concludes that the developed interactive teaching medium for solar system introduction is highly valid, feasible, and ready for implementation. This research contributes to the provision of an innovative teaching aid for teachers and serves as a foundation for further studies to empirically examine the medium’s effectiveness in classroom settings.